The new digital infiltration profiler performance test on sandy soil - Faris, Fikri (Springer Verlag, 2022)
A more accurate monitoring system needs to be developed by calculating the infiltration process of rainwater into the soil. The development of a digital infiltration profiler (DIP) is expected to be able to improve the accuracy of the early warning system, as well as to open a more considerable opportunity to study the landslide mechanism related to the infiltration process and the increase of pore-water pressure in the soil at both field-scale and laboratory scale. The performance and reliability of developed DIP was tested through laboratory and field ponding simulation. The field testing was demonstrated through a real installment procedures to be applied in the actual case. The field testing also consisted of water ponding and data reading. Numerical simulation using SEEP/W software of Geostudio packages was conducted to be compared to the field-testing data. From the laboratory ponding experiment, the sensor readings correspond well to the wetting front observation. The field ponding observation results showed good response of the DIP in detecting the wetting front. The results also implied the similarity of reducing wetting front rate that was simulated in SEEP/W and previous studies. The coupled numerical simulation and slope stability analysis of the conceptual slope model suggested the importance of multi-depth saturation measurement is necessary. The near-surface observation needs to confirm the saturation of the soil surface. The deeper sensor can continuously monitor soil saturation change in prolonged rainfall to predict the safety factor of the slope. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.